2014
DOI: 10.1353/cpr.2014.0013
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Needs in Community-Based Organizations for Enhancing Translational Research in Puerto Rico

Abstract: Background-In an effort to form and sustain community-academic partnerships (CAPs) to enhance clinical and translational research, an assessment of needs for selecting and implementing evidence-based programs (EBPs) was conducted among a group of community-based organizations (CBOs) throughout Puerto Rico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Our assessment of COs' needs relative to advancing their research agendas showed that we are addressing many of the reported needs, and that opportunities remain; both important outcomes for our purpose of providing relevant research capacitybuilding support. For example, many of the partnering and research planning/evaluation needs, which are also consistent with needs of other COs, [10][11][12] are addressed as part of the Forums described here and our Community Research Day. Community Research Day is designed to connect COs with potential academic research partners via an interactive poster/networking session where the organizations' missions and research needs are highlighted.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our assessment of COs' needs relative to advancing their research agendas showed that we are addressing many of the reported needs, and that opportunities remain; both important outcomes for our purpose of providing relevant research capacitybuilding support. For example, many of the partnering and research planning/evaluation needs, which are also consistent with needs of other COs, [10][11][12] are addressed as part of the Forums described here and our Community Research Day. Community Research Day is designed to connect COs with potential academic research partners via an interactive poster/networking session where the organizations' missions and research needs are highlighted.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, relative to the training needs reported here and documented by others in reference to planning, implementation, and evaluation, 10,12,13 we off er face-to-face group training sessions that were codeveloped and pilot tested with various community partners (e.g., an IRB approved training called Research Ethics for Community Partners); we also off er individual research consultations, which are facilitated by community partners and CERC faculty and staff . Our research capacity-building eff orts also address the funding-related needs reported here and include the awarding of small grants, typically up to $5,000, for communityacademic research activities led by the community.…”
Section: Discussionmentioning
confidence: 99%